Longitudinal examination of weight-for-length and developmental screening results in infancy and toddlerhood. Issue 2 (3rd April 2021) - Odar Stough, Cathleen; Garr, Katlyn; Singh Khalsa, Amrik; Combs, Angela; Copeland, Kristen A.
ABSTRACT: The current study examined whether high infant weight-for-recumbent-length (WFL) percentile (i.e., ≥ 85th percentile) at 6 months of age longitudinally related to motor skills, problem solving, and personal/social outcomes on a developmental screener ( Ages and Stages Questionnaire-3 ) at 9 months and 18 months of age. Data were extracted from the medical record at a primary care clinic serving primarily low income and racial minority infants ( n = 538). WFL category at 6 months was not related to developmental screener outcomes at 9 or 18 months in both unadjusted analyses and adjusted analyses controlling for relevant covariates.